Insulin Resistance and the Risk of Diabetes and Dysglycemia in Korean General Adult Population - Jong Ha Baek; Hosu Kim; Kyong Young Kim; Jaehoon Jung (Diabetes & Metabolism Journal, 2018)
BackgroundInsulin resistance is a major pathogenic hallmark of impaired glucose metabolism. We assessed the accuracy of insulin resistance and cut-off values using homeostasis model assessment of insulin resistance (HOMA-IR) to classify type 2 diabetes mellitus (T2DM) and dysglycemia according to age and sex.MethodsIn this cross-sectional study, we analyzed 4,291 anti-diabetic drug-naïve adults (≥20 years) from the 6th Korea National Health and Nutrition Examination Survey in 2015. Metabolic syndrome (MetS) was defined by the modified National Cholesterol Education Program III guideline. Diagnosis of dysglycemia and T2DM were based on fasting glucose and glycosylated hemoglobin levels. The receiver operating characteristic curve and optimal cut-off values of HOMA-IR were assessed to identify T2DM/dysglycemia according to sex and were further analyzed by age.ResultsSex differences were found in the association of MetS and the different MetS components with T2DM/dysglycemia. The overall optimal cut-off value of HOMA-IR for identifying dysglycemia was 1.6 in both sex. The cut-off values for T2DM were 2.87 in men and 2.36 in women. However, there are differences in diagnostic range of HOMA-IR to distinguish T2DM according to sex and age, and the accuracy of HOMA-IR in identifying T2DM gradually decreased with age especially in women.ConclusionInsulin resistance is closely associated with the risk for T2DM/dysglycemia. The accuracy of HOMA-IR levels is characterized by sex- and age-specific differences in identifying T2DM. In addition to insulin resistance index, insulin secretory function, and different MetS components should be considered in the detection of early T2DM, especially in elderly.